From melies to new media : spectral projections - Haslem, Wendy (Intellect, 2019)
From Méliès to New Media contributes to a dynamic stream of film history that is just beginning to understand that new media forms are not only indebted to, but firmly embedded within the traditions and conventions of early film culture. Adopting a media archaeology, this book will present a comparative examination of cinema including early film experiments with light and contemporary music videos, silent film and their digital restorations, German Expressionist film and post-noir cinema, French Gothic film and the contemporary digital remake, Alfred Hitchcock's films exhibited in the gallery, post medium films as abstracted light forms and interactive digital screens revising experiments in precinema. Media archaeology is an approach that uncovers the potential of intermedial research and, as a fluid form of history. It envisages the potential of new discoveries that foreground forgotten or marginalized contributions to history. It is also an approach that has been championed by influential new historicists like Thomas Elsaesser as providing the most vibrant and productive new histories (2014).